The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4049/jimmunol.174.12.7654
|View full text |Cite
|
Sign up to set email alerts
|

CD8 Cell Division Maintaining Cytotoxic Memory Occurs Predominantly in the Bone Marrow

Abstract: Long-term persistence of Ag-experienced CD8 cells, a class of T lymphocytes with cytotoxic function, contributes to immunological memory against intracellular pathogens. After Ag clearance, memory CD8 cells are maintained over time by a slow proliferation, primarily cytokine driven. In this article, we show that the bone marrow (BM) is the crucial organ where such basal division of memory CD8 cells occurs. BM memory CD8 cells contain a higher percentage of proliferating cells than their corresponding cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
162
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(190 citation statements)
references
References 71 publications
(82 reference statements)
23
162
5
Order By: Relevance
“…Another indication for homeostatic proliferation of splenic memory T cells had come from analyses of the uptake of bromodeoxyuridine (BrdU) into their DNA, taken as a surrogate marker for proliferation 110, 111, 113. In those experiments, about 50% of the splenic memory CD8 + T cells had incorporated BrdU within 14 days.…”
Section: The Bone Marrow—hub For Circulating or Home Of Resident Memomentioning
confidence: 99%
“…Another indication for homeostatic proliferation of splenic memory T cells had come from analyses of the uptake of bromodeoxyuridine (BrdU) into their DNA, taken as a surrogate marker for proliferation 110, 111, 113. In those experiments, about 50% of the splenic memory CD8 + T cells had incorporated BrdU within 14 days.…”
Section: The Bone Marrow—hub For Circulating or Home Of Resident Memomentioning
confidence: 99%
“…Moreover, global transcription data, CD69 expression profiles and colocalization in tissue sections do not address in vivo T cell migration. In fact, in situ-labelling studies and parabiosis experi ments have shown that memory T cells do recirculate to and from the bone marrow 5,6 .In conclusion, the available evidence supports the view that the bone marrow is a 'stopping point' where recirculating memory CD8 + T cells are stimulated to proliferate before continuing to move around the body 3,4,12,13 . Notably, lodging into the bone marrow is a competitive process among memory T cells 14 , which is an element to be considered especially in interpretation of adoptive transfer data 11,14 .…”
mentioning
confidence: 52%
“…This view was in contrast with the largely accepted notion at the time that recirculating memory T cells are maintained by a homeostatic equilibrium between proliferation and death long after antigen clearance 2 . Furthermore, it did not accommodate previous data concerning the proliferation 3,4 and recirculation 5,6 of memory CD8 + T cells in the bone marrow.…”
Section: Francesca DI Rosamentioning
confidence: 64%
See 2 more Smart Citations